Arbuscular mycorrhizal fungi in European grasslands under nutrient pollution. Issue 12 (23rd August 2019) - Ceulemans, Tobias; Van Geel, Maarten; Jacquemyn, Hans; Boeraeve, Margaux; Plue, Jan; Saar, Liina; Kasari, Liis; Peeters, Gerrit; van Acker, Kasper; Crauwels, Sam; Lievens, Bart; Honnay, Olivier
Abstract: Aim: Our aim was to quantify the extent to which nutrient pollution explains arbuscular mycorrhizal fungal community richness and composition. Location: Europe. Time period: 2014–2016. Major taxa studied: Arbuscular mycorrhizal fungi. Methods: We sampled soils of calcareous and acidic grasslands and roots of 34 host plant species across a large geographical gradient of atmospheric nitrogen deposition and soil phosphorus availability. Furthermore, we performed an independent pairwise comparison between fertilized and unfertilized grasslands in Belgium and Iceland to compare results. Results: We found that nitrogen deposition had a significant negative relationship to arbuscular mycorrhizal fungal richness, with a negative community threshold of 7.7 kg N/ha/year corresponding to the greatest reduction in operational taxonomic units. Additionally, we found that soil phosphorus had a significant negative relationship to mycorrhizal fungal richness. Main conclusions: Our results highlight the necessity to revisit the critical loads of atmospheric nitrogen deposition used in European environmental policy, currently set at 10–15 kg N/ha/year. Importantly, our observed threshold of 7.7 kg N/ha/year does not correspond to a critical load below which there is no environmental harm, because the least negative changes in arbuscular mycorrhizal fungal communities were observed at < 5 kg N/ha/year. Therefore, to avoid compromising the policy tenet of no environmental harm with respect to grassland mycorrhizal fungi, areas of zero tolerance to nitrogen pollution should be delimited. Our results also indicate that environmental policy biased towards reducing nitrogen pollution alone will fail to preserve mycorrhizal biodiversity in European grasslands. We advocate increased policy attention to avoid phosphorus enrichment, particularly through agricultural fertilization. Here too, areas of zero phosphorus input, ideally set in the currently unpolluted (or least polluted) areas, seem key for effective environmental policy, because elevated levels of soil phosphorus after phosphorus fertilization are known to be extremely persistent.